Deconstruction Of The Meaning Of Polygamy In Women's Perspective In The Movie “Atas Nama Surga” - Hairiyah (International Journal of Sociology of Religion, 2024)
This study deconstructs the meaning of polygamy in the film “Atas Nama Surga” as an act of assertiveness by women `who reject polygamy, signifying the importance of maintaining women's strength and dignity. This study emphasizes women's perspectives, providing awareness of the importance of having the courage to speak one's mind. The research method uses a qualitative literature study with movie analysis from the MAXstream platform as primary data, and journals, books, articles, and online sources as secondary data. The results identify the deconstruction of polygamy as a cause of women's suffering, the potential for violence, and as a form of male selfishness. Factors such as experience, knowledge, and economic power influence the emergence of this deconstruction of meaning. The implications include stereotyping men as violent and selfish, polygamy being perceived as material control, and the difficulty of realizing a monogamous marriage. Despite the limited focus on one movie, this research provides a basis for extending the deconstruction to other works.